2016
DOI: 10.1111/tid.12471
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors of multidrug‐resistant bacteria in respiratory samples after lung transplantation

Abstract: A large proportion of MDR bacteria are detected on respiratory invasive samples in LT patients, and the risk of their emergence is mainly determined by the previous exposure to broad-spectrum antibiotics and the length of ICU stay. Adequate treatment requires broad-spectrum empiric antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…found that risk factors for MDROs in respiratory samples after lung transplantation include bilateral LT, mechanical ventilation >3 days, ICU LOS >14 days, the presence of a tracheostomy, and exposure to broad‐spectrum antibiotics. They also observed an increase in MDROs within the first 4 weeks of ICU hospitalization, indicating a need for an evaluation of the appropriateness of empiric antibiotics.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…found that risk factors for MDROs in respiratory samples after lung transplantation include bilateral LT, mechanical ventilation >3 days, ICU LOS >14 days, the presence of a tracheostomy, and exposure to broad‐spectrum antibiotics. They also observed an increase in MDROs within the first 4 weeks of ICU hospitalization, indicating a need for an evaluation of the appropriateness of empiric antibiotics.…”
Section: Discussionmentioning
confidence: 98%
“…This study did not capture whether the use of broad‐spectrum antibiotics early on, in a disease state that is prone to multiple infections, impacts drug resistance and what impact that might have on long‐term outcomes. A recent study by Tebano et al . found that risk factors for MDROs in respiratory samples after lung transplantation include bilateral LT, mechanical ventilation >3 days, ICU LOS >14 days, the presence of a tracheostomy, and exposure to broad‐spectrum antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low prevalence of MDR bacteria in our study reflects that Sweden still has a favorable situation regarding antimicrobial resistance compared to most countries. In comparison, Kovatz et al described a MRSA prevalence of 25% in lung transplant patients in the first post‐operative year, and Tebano et al found MDR strains in respiratory samples in 90 of 179 lung transplanted patients (51%). In a recent publication, Rodrigo‐Troyano et al describes the serious threat posed by Gram‐negative MDR bacteria in respiratory infections.…”
Section: Discussionmentioning
confidence: 98%